The implementation of Key Performance Indicators (KPIs) in the Malaysian public sector / Mahazril ‘Aini Yaacob and Adnan Aminuddin - Yaacob, Mahazril ‘Aini; Aminuddin, Adnan (Universiti Teknologi MARA, Shah Alam, 2011)
The use of Key Performance Indicators (KPIs) as a tool of performance measurement has been practiced by the private sectors several years ago. Only recently, public sectors adopted this approach in measuring their organizational as well as their individual performances in line with their agenda to improve their service delivery system. Thus, this paper aims to look at the implementation of Key Performance Indicators (KPIs) mainly in the Malaysian Public Sectors in measuring their performance. In response to the Government Circular in 2005, Malaysian Public Sectors have developed their own set of KPIs and observation has been made regarding this matter. To this end, semi-structured interview was conducted at the National Registration Department, Pulau Pinang to further explore the use of KPIs in this frontline agency and how they approach this performance measurement tools as one way to measure their performance. The findings reveal that the use of KPIs has been successful in measuring their organizational and individual performance as well. Though it is hard at the initial stage to adopt this approach, but after several years of implementation, the use of KPIs contributed to several improvements in their administration and services. Nevertheless, since this study is just an explanatory study, it provides limited insights into how organizational managers perceived the relevance and usefulness of key performance indicators in measuring the organizational performance. This paper concludes that the implementation of KPIs